2018
DOI: 10.3390/su10093332
|View full text |Cite
|
Sign up to set email alerts
|

Prefiguring Sustainability through Participatory Action Research Experiences for Undergraduates: Reflections and Recommendations for Student Development

Abstract: PAR-based UREs are undergraduate research experiences (UREs)—built into university-community partnerships—that apply principles of participatory action research (PAR) towards addressing community-defined challenges. In this paper, we advance PAR-based UREs as an action-oriented framework through which higher education institutions can simultaneously enact and advance the United Nations sustainable development agenda, while cultivating student development. We draw upon interdisciplinary scholarship on sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 70 publications
(91 reference statements)
0
27
1
1
Order By: Relevance
“…The Conference of Vice-chancellor of Spanish universities indicated that service-learning could be a tool for the development of sustainability in the university context [32,70]. Other authors have reflected on using Participatory Action Research to promote sustainability and SDGs [14]. Furthermore, in previous works, it has been defended that the final master/degree dissertations can be a very interesting tool for the development of this type of competences [55,71].…”
Section: Teaching Methodologymentioning
confidence: 99%
“…The Conference of Vice-chancellor of Spanish universities indicated that service-learning could be a tool for the development of sustainability in the university context [32,70]. Other authors have reflected on using Participatory Action Research to promote sustainability and SDGs [14]. Furthermore, in previous works, it has been defended that the final master/degree dissertations can be a very interesting tool for the development of this type of competences [55,71].…”
Section: Teaching Methodologymentioning
confidence: 99%
“…The transition to Education for Sustainable Development (ESD) is a frequently addressed topic in the recent literature [1,[4][5][6]. Adopting innovative pedagogies in higher education has become one of the transition factors of ESD [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has theoretical and practical implications as follows. Most previous papers have discussed the readiness for teaching from a more general perspective [4,7,12,13,21] or have narrowed down the approach to a small set of teaching components or education levels (e.g., motivation, instructional strategies, and sustainability in primary education) [2,6,22,23,42,46,48]. In this paper, our focus was on a comprehensive approach of pre-service teachers' job readiness from an ESD perspective.…”
mentioning
confidence: 99%
“…En términos generales, los autores consideran positivos los resultados de aprendizaje de los estudiantes, alegando un amplio abanico de motivos. En algunos casos, señalan que aprovechar la comunidad como aliada proporcionaba al profesorado y estudiantado una pluralidad de puntos de vista, acceso a nuevos recursos e instalaciones y un gran acervo de habilidades y conocimientos (Powers, 2004;Linnemanstons y Jordan, 2017;Singer y Macdonald, 2017;Warr Pedersen et al, 2017;Trott et al, 2018;Williams, 2018).…”
Section: Los Resultados De Aprendizajeunclassified